Theoretical Study of Xanthone Derivative Corrosion Inhibitors Using Density Functional Theory (DFT) - Fitria Ramadhani; Emriadi Emriadi; Syukri Syukri (Syarif Hidayatullah State Islamic University, 2020)
The potential corrosion inhibitor properties of xanthone compounds and its derivatives (gartanin, 8-desoxygartanin, α-mangostine, and β-mangostine) can be demonstrated through Density Functional Density Theory (DFT) at the theoretical level B3LYP/6-31G(d, p). Quantum chemical parameters such as the energy of the highest molecular orbital occupied by electrons (EHOMO), the energy of the lowest molecular orbitals not occupied by electrons (ELUMO), energy gap (Egap / ΔE), dipole moment (µ), and total energy (Etot) can be calculated using DFT method. The DFT data analysis equation can determine the value; potential energy (I), electron affinity (A), absolute electronegativity (χ), global hardness (η), global softness (σ), number of transfer electrons (ΔN), electrophilicity (ω), and corrosion inhibition efficiency (IE%) . The results of quantum chemical parameter calculations show the potential inhibitory properties of gartanin > α-mangostine > β-mangostine > 8-desoxygartanin > xanthone, with the calculated corrosion inhibition efficiency value of gartanin of 86.54%.